Method for manufacturing separator for power storage device

Through a multi-step manufacturing method, including lamination molding, stretching treatment and heat treatment, the crystal structure and dispersion state of polyethylene and polypropylene are optimized, and the problem of unmelted residue in the battery separator is solved and the circulation performance and energy density of the battery is improved.

JP7674292B2Active Publication Date: 2025-05-09ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022026041
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-13
Filing Date
2022-02-22
Publication Date
2025-05-09
Estimated Expiration
2041-04-13

AI Technical Summary

Technical Problem

In the prior art, when manufacturing battery separators, there is a problem of unmelted residue when mixing and extruding various raw materials, resulting in defects such as aggregates and gels in the separators, affecting the cycling performance of the battery.

Method used

Using a method of manufacturing a separator, including lamination molding, stretching treatment, removal of plasticizers, heat treatment and winding, a variety of polymers such as polyethylene and polypropylene are used to optimize the microstructure of the separator by controlling their crystal structure and dispersion state.

Benefits of technology

It effectively reduces the defects of raw material mixing and extrusion, improves the circulation performance of the diaphragm and the energy density of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007674292000001
    Figure 0007674292000001
  • Figure 0007674292000002
    Figure 0007674292000002
  • Figure 0007674292000003
    Figure 0007674292000003
Patent Text Reader

Abstract

An object of the present invention is to provide a separator for an electricity storage device that has excellent cycle characteristics by reducing the drawbacks of the raw material mixing and extrusion process. [Solution] A method for manufacturing a separator for an electrical storage device is provided, which includes a step of extruding powdered polyethylene, pelletized polypropylene, and a plasticizer into a sheet using an extruder to form a molded body, and a step of making the molded body porous using a wet method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for an electricity storage device and a method for producing the same. [Background technology]

[0002] Microporous membranes are widely used as microfiltration membranes, fuel cell separators, condenser separators, base materials for functional membranes in which functional materials are filled into the pores to exhibit new functions, and separators for electricity storage devices, or as constituent materials thereof, etc.

[0003] Lithium ion secondary batteries (LIBs) are widely used in notebook personal computers, mobile phones, digital cameras, and the like. Among these, polyolefin microporous membranes are known as separators for LIBs or their constituent materials. Patent Document 1 proposes a method for producing a polyolefin microporous membrane with the aim of achieving high strength, a large specific surface area, and a large pore volume. Patent Document 1 proposes a method for producing a polyolefin microporous membrane by melt-kneading a polyolefin resin having a weight-average molecular weight of 500,000 or more with liquid paraffin, and extracting the liquid paraffin from the obtained resin composition to produce a polyolefin microporous membrane. Patent Document 2 describes a method for producing a microporous membrane by kneading a polyolefin resin such as polyethylene and a resin other than polyolefin (e.g., polyamide) in an extruder in advance to form pellets, mixing the pellets with liquid paraffin, extruding, and further extracting the liquid paraffin. Patent Documents 3 to 5 also describe a method for producing a LIB separator including a conventional process for producing a polyolefin microporous membrane.

[0004] In recent years, research has been conducted into increasing the capacity and energy density of LIBs in order to enable electric vehicles to travel long distances. For example, Non-Patent Document 1 shows that the energy density of LIBs can be significantly improved by increasing the nickel content in the NMC metal oxides, which are the positive electrode materials, and by incorporating a high concentration of silicon into graphite, which is the negative electrode material, or by completely replacing it with silicon.

[0005] On the other hand, Non-Patent Document 2 discloses that the silicon (high-concentration) negative electrode expands and contracts in volume by storing or releasing lithium ions during charging and discharging. Furthermore, Non-Patent Document 3 describes that the silicon (high-concentration) negative electrode repeatedly forms gaps around the silicon particles when expanding and contracting during charging and discharging, and the solid electrolyte interface (SEI) accumulates in the gaps, causing the silicon (high-concentration) negative electrode to expand irreversibly with long-term cycle use. As a result, the separator film is repeatedly subjected to compression force and the force is released, which may destroy (crush) the pore structure of the film or cause irreversible compression, resulting in a decrease in ion permeability. In particular, in the latter case (the phenomenon described in Non-Patent Document 3), it is theoretically difficult to suppress the generation of SEI in lithium-ion batteries composed of various non-aqueous electrolyte solutions.

[0006] In addition, Wu et al. report the Kuhn chain, which is a representative concept of the three-dimensional arrangement of polymer chains, in Non-Patent Document 4. Non-Patent Document 5 reports research on improving the mechanical properties of resin films using mixed resin systems, including control of the size or interparticle distance of different particles dispersed in a resin structure, and improvement of mechanical properties by a dispersion structure exceeding a specific degree of dispersion. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2002-088189 A [Patent Document 2] JP 2002-226639 A [Patent Document 3] International Publication No. 2020 / 067161 [Patent Document 4] JP 2020-092068 A [Patent Document 5] International Publication No. 2011 / 118660 [Non-patent literature]

[0008] [Non-Patent Document 1] Chem.Rev.2018,118,11433-11456 [Non-Patent Document 2] J.Phys.Chem.C 2014,118,9395-9399 [Non-Patent Document 3] ACS Appl.Mater.Interfaces 2019,11,45726-45736 [Non-Patent Document 4] Journal of Polymer Science:Part B:Polymer Physics,Vol.27,723-741(1989) [Non-Patent Document 5] POLYMER,1985,Vol 26,November 1855 Summary of the Invention [Problem to be solved by the invention]

[0009] In recent years, there has been a demand for reducing defects (i.e., the amount of unmelted material) that occur during the mixing and extrusion process of multiple raw materials when producing microporous membranes as a constituent material of separators for power storage devices. Unmelted material during the mixing and extrusion process can cause agglomerates and gels in the final microporous membrane. It is expected that separators equipped with microporous membranes with reduced defects can realize power storage devices with excellent capacity retention characteristics (cycle characteristics) when repeatedly charged and discharged.

[0010] However, the microporous membranes described in Patent Documents 1 and 2 have drawbacks in the raw material mixing / extrusion process and have room for improvement in terms of the cycle characteristics of an electricity storage device equipped with a separator. Moreover, none of Patent Documents 3 to 5 focuses on the form of the resin raw material in the melt-kneading process or the extrusion process, and does not describe in detail the effect of the type or structure of the polyolefin in the separator for an electricity storage device on the cycle characteristics.

[0011] In view of the above circumstances, an object of the present invention is to provide a separator for an electricity storage device that is excellent in cycle characteristics by reducing the drawbacks of the raw material mixing and extrusion process. [Means for solving the problem]

[0012] The present inventors have conducted studies to solve the above problems, and have found that the above problems can be solved by using a method for producing a separator for an electricity storage device having the following configuration, thereby completing the present invention. Some aspects of the present invention are exemplified below. [1] The process is as follows: (1) A sheet forming process in which polypropylene, polyethylene, and a plasticizer are extruded into a sheet using an extruder, cooled and solidified, and processed into a sheet-shaped molded product; (2) a stretching step of stretching the sheet-like molded body at an areal magnification of 20 times or more and 250 times or less to form a stretched product; (3) extracting the plasticizer from the stretched product to form a microporous membrane; (4) a heat treatment step of subjecting the microporous membrane to a heat treatment to stretch and relax it in the width direction to obtain a heat-treated microporous membrane; and (5) a winding step of winding the heat-treated microporous membrane; A method for producing a separator for an electricity storage device, comprising: The method for producing a separator for an electrical storage device, wherein the polyethylene is in a powder form and the polypropylene is in a pellet form. [2] The polypropylene and the polyethylene are prepared by the following methods (a) to (c): (a) feeding the polypropylene and the polyethylene into the extruder using separate feeders; (b) A method in which the polypropylene and the polyethylene are dry-blended and then fed into an extruder using a single feeder; (c) A method in which a plurality of resin raw materials obtained by dry blending the polypropylene and the polyethylene are fed into an extruder using separate feeders; 2. The method for producing an electricity storage device separator according to item 1, wherein the separator is fed into the extruder by any one of the following methods. [3] 3. The method for producing a separator for an electricity storage device according to item 1 or 2, wherein a mass ratio of the polyethylene to the polypropylene is 99 / 1 to 60 / 40. [4] 4. The method for producing a separator for an electricity storage device according to item 3, wherein the polyethylene has a weight average molecular weight (Mw) of 100,000 to 9,700,000 and a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 3 to 12. [5] The polypropylene has a weight average molecular weight (Mw) of 300,000 to 2,000,000 and a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 3 to 12; 4. The method for producing a separator for an electricity storage device according to item 3, wherein the polypropylene has an isotactic pentad fraction (mmmm) of 85.0 mol % to 99.7 mol %. [6] 6. A separator for an electricity storage device, produced by the production method according to any one of items 1 to 5. [7] The separator for the electricity storage device includes a microporous membrane, The microporous membrane comprises polyethylene and polypropylene; In the X-ray diffraction (XRD) or wide-angle X-ray scattering (WAXS) measurement of the microporous membrane, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 15 nm to 40 nm. 7. The separator for an electricity storage device according to item 6, wherein the crystallite size of the polyimide is 10 nm to 50 nm. [8] A separator for an electricity storage device comprising a microporous membrane, The microporous membrane comprises polyethylene and polypropylene; A separator for an electricity storage device, wherein, in an X-ray diffraction (XRD) measurement of the microporous film, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 10 nm to 50 nm. [9] 9. The separator for an electricity storage device according to item 8, wherein, in an XRD measurement of the microporous membrane, the crystallinity of the polyethylene is 55% to 99.9%.

[10] A separator for an electricity storage device comprising a microporous membrane, The microporous membrane comprises polyethylene and polypropylene; A separator for an electricity storage device, wherein, in a wide-angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 10 nm to 50 nm.

[11] Item 11. The separator for use in an electricity storage device according to item 10, wherein, in a WAXS measurement of the microporous membrane, the degree of crystallinity of the polyethylene is 50% to 90%.

[12] 12. The separator for an electricity storage device according to any one of items 8 to 11, wherein the polypropylene contained in the microporous membrane has an isotactic pentad fraction (mmmm) of 85.0 mol % to 99.7 mol %.

[13] 13. A battery comprising the separator for an electricity storage device according to any one of items 6 to 12. Effect of the Invention

[0013] According to the present invention, it is possible to provide a method for producing a microporous membrane or a separator for an electricity storage device that reduces the defects of the raw material mixing and extrusion process. Also, according to the present invention, it is possible to provide an electricity storage device with excellent cycle characteristics by reducing the amount of aggregates or gel content in the separator for an electricity storage device obtained by the production method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments, and various modifications are possible within the scope of the gist of the present invention. In this specification, unless otherwise specified, "to" means that the numerical values ​​at both ends are the upper limit and the lower limit. In addition, in this specification, the upper limit and the lower limit of the numerical range can be arbitrarily combined.

[0015] A first embodiment of the present invention provides a separator for an electricity storage device including a microporous membrane, and specifies the crystal structure of a resin component constituting the microporous membrane. A second embodiment of the present invention provides a method for producing a separator for an electricity storage device including a microporous membrane, and specifies the raw materials used in the production method. Each embodiment will be described later.

[0016] <Separators for power storage devices> One embodiment of the present invention provides a separator for an electricity storage device. The separator for an electricity storage device (hereinafter sometimes abbreviated as "separator") refers to a member that is disposed between a plurality of electrodes in an electricity storage device and has ion permeability and, if necessary, a shutdown property.

[0017] The separator may be in the form of a flat membrane (e.g., formed from a single microporous membrane), a laminated membrane (e.g., a laminate of multiple microporous membranes, or a laminate of a microporous membrane and another membrane), a coated membrane (e.g., a microporous membrane having at least one surface coated with a functional substance), or the like.

[0018] The separator according to the first embodiment includes a microporous film containing polyethylene (PE) with a crystallite size of 15 nm to 40 nm and polypropylene (PP) with a crystallite size of 10 nm to 50 nm. The crystallite size can be measured by a known method, for example, by X-ray diffraction (XRD) using a reflection type X-ray diffractometer such as Ultima-IV manufactured by Rigaku Corporation, or by wide-angle X-ray scattering (WAXS) using a transmission type X-ray scattering device such as NANOPIX. The components of the separator are described below.

[0019] <Microporous membrane> The microporous membrane can be used as a precision filtration membrane, a fuel cell separator, a capacitor separator, a power storage device separator, an electrolysis membrane, or a constituent material thereof, and the like. When a microporous membrane is used as a separator for an electricity storage device or a constituent material thereof, particularly as a separator for a LIB or a constituent material thereof, the microporous membrane itself may be used as the separator, or a microporous membrane having another layer or membrane provided on at least one side thereof may be used as the separator. The microporous membrane used for the separator for an electricity storage device preferably has low electronic conductivity, ionic conductivity, high resistance to organic solvents, and fine pores.

[0020] From the viewpoint of shutdown characteristics when used as a separator for an electricity storage device, the microporous membrane is preferably formed of 50% by mass to 100% by mass of polyolefin (PO), and the PO ratio is more preferably 60% by mass to 100% by mass, and further preferably 70% by mass to 100% by mass. From the viewpoint of thermal membrane rupture resistance and reduction in pore size, the microporous membrane preferably contains both polyethylene (PE) and polypropylene (PP) as PO.

[0021] The microporous membrane of the first embodiment contains PE with a crystallite size of 15 nm to 40 nm and PP with a crystallite size of 10 nm to 50 nm, which is believed to mean the formation of a microporous membrane in which the crystalline states of PE and PP are appropriately distributed.

[0022] Furthermore, a microporous membrane having an appropriate crystal distribution of PE and PP is more likely to recover its volume in the direction of compression due to swelling of the electrolyte, and is more likely to deform in response to the expansion and contraction of a negative electrode such as a silicon-containing negative electrode (i.e., the pore size of the microporous membrane is more likely to decrease even if the membrane is reduced), compared with separators for conventional silicon (high-concentration) negative electrodes as described in Non-Patent Documents 1-3, and / or the separator is in close contact with the negative electrode when the silicon-containing negative electrode contracts, which makes it difficult for gaps to form between the two and tends to suppress the deposition and growth of excess solid electrolyte interface (SEI) on the surface of the negative electrode, thereby improving the cycle during long-term use in an electricity storage device. On the other hand, the appropriate crystal distribution of PE and PP suggests that the disadvantages of the mixing and extrusion process of the resin raw materials in the manufacturing process of the microporous membrane are reduced. From this viewpoint, the combination of the crystallite sizes of PE and PP is preferably a PE crystallite size of 16 nm to 39 nm and a PP crystallite size of 11 nm to 49 nm, more preferably a PE crystallite size of 20 nm to 38 nm and a PP crystallite size of 11 nm to 47 nm.

[0023] An appropriate crystal distribution of PE and PP in a microporous membrane can be achieved, for example, by specifying the respective states of PE and PP during the mixing and extrusion process of the resin raw materials, or by controlling the stereoregular structure of PP, such as the isotactic pentad fraction (mmmm).

[0024] (Polyethylene (PE)) The polyethylene (PE) preferably has a weight average molecular weight (Mw) of 100,000 to 9,700,000 and / or a ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) of 3 to 12. PE resins with such Mw and Mw / Mn are also called ultra-high molecular weight polyethylene (UHMWPE), and are preferred from the viewpoints of optimizing the crystal distribution, aggregate amount and gel content of a microporous membrane containing PE and PP, and the cycle characteristics of a separator and an electricity storage device using the same.

[0025] From the same viewpoints as above, the Mw of PE is more preferably 120,000 to 9,000,000, and further preferably 200,000 to 8,500,000. The dispersity (Mw / Mn) is more preferably 4 to 11, and further preferably 5 to 10.

[0026] From the viewpoint of the swelling state due to the electrolyte in the battery, the crystallinity of the PE alone measured by the XRD method is preferably 55% to 99.9%, more preferably 80% to 99.8%, and even more preferably 85% to 97%. From the same viewpoint, the crystallinity of the PE alone measured by the WAXS method is preferably 50% to 90%, more preferably 65% ​​to 80%, and even more preferably 68% to 77%. The XRD method and the WAXS method have differences in the measurement results of crystallite size and crystallinity obtained even when measuring the same microporous membrane, and the difference often tends to be noticeable in the crystallinity measurement. It is presumed that such differences are due to the following. The XRD method is a reflection type measurement, and the measurement results are mainly information on the surface of the microporous membrane. On the other hand, the WAXS method is a transmission type measurement, and the measurement results are averaged information including the surface and internal structure of the microporous membrane. In the production process of the microporous membrane described herein, cooling and heating are performed from the surface, and sheeting and stretching are performed, and therefore it is acceptable for the surface of the obtained microporous membrane to tend to be more crystallized. In such a PE crystal group, the entire higher-order structure via the crystals is likely to swell (permeate, internally diffuse) due to thermal energy such as molecular vibration of the electrolyte in the temperature range of the battery used (-30°C to 80°C), which is thought to lead to a good volume recovery rate in the compression direction. Swelling into the PE crystal structure is a phenomenon that occurs when the penetration force of the electrolyte is higher than the force based on the entropy elastic energy of the higher-order structure of PE. Therefore, swelling into the higher-order structure of PE requires improving the penetration force of the electrolyte or constructing a higher-order structure of PE that is likely to swell with the electrolyte (a higher-order structure of PE that can stabilize the entire higher-order structure heat in terms of thermal energy after swelling). In the present invention, a higher-order structure of PE that is likely to swell could be constructed while maintaining the mechanical strength of the microporous membrane within the temperature range of the battery used. In line with this tendency, the PE crystallite size is preferably 15nm to 40nm, more preferably 16nm to 39nm, and even more preferably 20nm to 38nm. The crystallite size of PE alone can be adjusted to within the above numerical range, for example, by controlling the PE form or the PE raw material charging method in the microporous membrane production process, or by specifying the ratio of the PE raw material to the polypropylene (PP) raw material.

[0027] The PE may contain not only a single type but also multiple types of UHMWPE. From the viewpoint of high strength of the microporous membrane, the UHMWPE is preferably poly(ethylene and / or propylene-co-α-olefin), more preferably at least one selected from the group consisting of poly(ethylene-co-propylene), poly(ethylene-co-butene), and poly(ethylene-co-propylene-co-butene). From the same viewpoint, the UHMWPE preferably contains 98.5 mol% or more and 100 mol% or less of constitutional units derived from ethylene, and more preferably contains more than 0.0 mol% and 1.5 mol% or less of constitutional units derived from α-olefins other than ethylene.

[0028] The PE may also contain a polyethylene resin other than UHMWPE. Examples of the polyethylene resin other than UHMWPE include low-density polyolefins (LDPE) such as linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), high-pressure low-density polyethylene, and mixtures thereof.

[0029] (Polypropylene (PP)) The polypropylene (PP) preferably has a weight average molecular weight (Mw) of 300,000 to 2,000,000 and a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 3 to 12. A PP resin with such Mw and Mw / Mn is preferable from the viewpoints of optimizing the crystal distribution of a microporous membrane containing PE and PP, the amount of aggregates and gel content, and the cycle characteristics of a separator and an electricity storage device using the same.

[0030] From the same viewpoints as above, the Mw of PP is more preferably 305,000 to 1,900,000, and even more preferably 310,000 to 1,800,000. The dispersity (Mw / Mn) is more preferably 4 to 11, and even more preferably 4.5 to 10.

[0031] The crystallite size of PP alone is preferably 10 nm to 50 nm, more preferably 11 nm to 49 nm, and even more preferably 11 nm to 47 nm, from the viewpoint that the microporous film containing PE and PP has good volume recovery in the compression direction due to electrolyte swelling in the battery. Since PP is incompatible with PE, it is possible to construct a mixed crystal system in which PP is finely dispersed in the network structure of PE without forming a mixed crystal with PE. As shown in Non-Patent Document 5, a dispersion structure exceeding a certain degree of dispersion by controlling the size or interparticle distance of different particles dispersed in a resin structure can significantly improve mechanical properties such as impact strength, and it is known that such a phenomenon is controlled by the size of several hundred nm to several μm for the dispersed different particles. In contrast, in this embodiment, it is surprisingly found that the crystal structure of PE and PP, which has never been seen before, can be controlled, not by particles, but by a significantly small order of several tens of nm, to improve the mechanical properties of the volume recovery in the compression direction of the separator. The crystallite size of the PP alone can be adjusted to within the above numerical range, for example, by controlling the PP form or the PP raw material charging method in the microporous membrane production process, specifying the ratio of the PP raw material to the polyethylene (PE) raw material, etc.

[0032] From the viewpoint of heat resistance and melt viscosity, PP is preferably a propylene homopolymer. Examples of PP include isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, etc. Among them, isotactic polypropylene is preferable. The amount of isotactic PP is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 100% by mass (all) based on the total mass of PP in the microporous membrane.

[0033] From the viewpoint of optimizing the crystal distribution of PE and PP in the microporous membrane, the isotactic pentad fraction (mmmm) regarding the stereoregular structure (pentad sequence) of PP is preferably 85.0 mol% to 99.7 mol%, more preferably 86.0 mol% to 99.6 mol%, and even more preferably 87.0 mol% to 99.5 mol%.

[0034] From the viewpoint of optimizing the crystal distribution of PE and PP in the microporous membrane, among the pentad sequences of PP, (mmmr) is preferably 0.5 mol % to 2.5 mol %, and more preferably 0.9 mol % to 2.4 mol %.

[0035] From the same viewpoint as above, among the pentad sequences of PP, (rmmr) is preferably 0.1 mol % to 1.0 mol %, and more preferably 0.1 mol % to 0.6 mol %.

[0036] From the same viewpoint as above, in the pentad sequences of PP, (mmrr) is preferably 0.3 mol % to 2.5 mol %, and more preferably 0.5 mol % to 2.3 mol %.

[0037] From the same viewpoint as above, in the pentad sequences of PP, (mmrm+rrmr) is preferably 0.5 mol % to 1.5 mol %, and more preferably 0.7 mol % to 1.3 mol %.

[0038] From the same viewpoint as above, in the pentad sequences of PP, (mrmr) is preferably 0.5 mol % or less, and more preferably 0.4 mol % or less.

[0039] From the same viewpoint as above, among the pentad sequences of PP, (rrrr) is preferably 0.1 mol % to 1.5 mol %, and more preferably 0.2 mol % to 1.2 mol %.

[0040] From the same viewpoint as above, among the pentad sequences of PP, (rrrm) is preferably 0.1 mol % to 1.5 mol %, and more preferably 0.2 mol % to 1.0 mol %.

[0041] From the same viewpoint as above, in the pentad sequence of PP, (mrrm) is preferably 0.1 mol % to 1.5 mol %, and more preferably 0.2 mol % to 1.0 mol %.

[0042] A structure in which the methyl groups of polypropylene units are linked in the same direction is known as meso (m), and a structure in which they are linked in opposite directions is known as racemo (r). In this embodiment, by using PP composed of at least one stereoconfiguration of mmmm to mrrm at a limited ratio as described above, a phenomenon is observed in which the crystal distribution with PE can be excellently adjusted in the production of a microporous membrane.

[0043] For this phenomenon to occur, it is important that the dissolved PE and PP are well dispersed at the molecular level in the presence of a plasticizer, and in particular, control of the entanglement state of the PP molecular chains is required. As shown in Non-Patent Document 4, Wu et al. report that the representative concept for the three-dimensional configuration of polymer chains is the Kuhn chain model, and that a certain number of units of the monomer are bent to determine the three-dimensional configuration of the polymer chain. In the Kuhn chain model, a "node" represents an atom between bonds, and in the case of PP, it represents a C atom, and "l k " is the bond length, and in the case of PP, it is the distance between C atoms. Based on this model, a theoretical formula is derived to calculate the three-dimensional angle between segments and the distance between the two ends of the polymer chain, and it is revealed that the entanglement structure of the molecular chain can be logically depicted. In this embodiment, the proportion of mmmm configuration in PP is experimentally determined, and such PP is presumed to have a radius of gyration that shows good dispersibility with PE in a plasticizer.

[0044] (PE to PP mass ratio) The mass ratio of polyethylene to polypropylene is preferably 99 / 1 to 60 / 40, more preferably 97 / 3 to 70 / 30, even more preferably 95 / 5 to 85 / 15, and most preferably 93 / 7 to 90 / 10, as the PE / PP mass ratio. It is presumed that by adjusting the PE / PP mass ratio in the microporous membrane within the above numerical range, PP is uniformly dispersed in PE. In reality, it is difficult to uniformly disperse PP in PE by simply mixing the PE raw material and the PP raw material in the manufacturing process of the microporous membrane. Although not wishing to be bound by theory, in the manufacturing process of the separator for the electric storage device described later, the above-mentioned suitable dispersion tends to be obtained by controlling the form or raw material input method of the PE raw material and the PP raw material and subjecting them to a special extrusion process. And, according to such a method, it becomes easier to disperse PP in PE more suitably at the above-mentioned mass ratio.

[0045] (Other Ingredients) The microporous membrane may contain a polyolefin (PO) resin other than PE and PP, such as a butylene homopolymer having excellent crystallinity, within the scope of not impeding the effect of the present invention.

[0046] Furthermore, the microporous membrane may contain, as a resin component other than PO, for example, polyamide resins such as nylon 6, nylon 66, nylon 11, nylon 6-10, nylon 6-12, nylon 6-66, and aramid resin; polyimide-based resins; polyester-based resins such as polyethylene terephthalate (PET) and polybutene terephthalate (PBT); fluorine-based resins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); copolymers of ethylene and vinyl alcohol (for example, EVAL manufactured by Kuraray Co., Ltd., melting point: 157°C to 190°C), polysulfone, polyethersulfone, polyketone, polyetheretherketone (PEEK), etc., within a range that does not impair the effects of the present invention. These resin components may be used singly or in a plurality of combinations.

[0047] The microporous membrane may contain additives other than the resin, as long as the additives do not impair the effects of the present invention, such as a dehydration condensation catalyst, metal soaps such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a color pigment.

[0048] (Various characteristics of microporous membranes) The properties of the microporous membrane are described below. These properties are measured when the microporous membrane used as the electricity storage device separator is a flat membrane. When the electricity storage device separator is in the form of a laminated membrane, the properties can be measured after removing layers other than the microporous membrane from the laminated membrane.

[0049] The porosity of the microporous membrane is preferably 20% or more, more preferably 30% or more, and even more preferably 32% or more or 35% or more. When the microporous membrane has a porosity of 20% or more, the membrane tends to have improved compliance with rapid movement of alkali metal ions when used as an alkali metal ion battery separator or a constituent material thereof. On the other hand, the porosity of the microporous membrane is preferably 90% or less, more preferably 80% or less, and even more preferably 50% or less. When the microporous membrane has a porosity of 90% or less, the membrane strength tends to be improved and self-discharge tends to be suppressed. The porosity of the microporous membrane is measured by the method described in the Examples.

[0050] The air permeability of the microporous membrane is 100 cm 3 The air permeability of the microporous membrane is preferably 1 second or more, more preferably 50 seconds or more, even more preferably 55 seconds or more, and even more preferably 100 seconds or more per second. When the air permeability of the microporous membrane is 1 second or more, the balance between the membrane thickness, the porosity, and the average pore size tends to be improved. In addition, the air permeability of the microporous membrane is preferably 400 seconds or less, more preferably 300 seconds or less. When the air permeability of the microporous membrane is 400 seconds or less, the ion permeability tends to be improved. The air permeability of the microporous membrane can be adjusted by adjusting the stretching ratio, the stretching temperature, etc. Such air permeability is measured by the method described in the Examples.

[0051] The thickness of the microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, even more preferably 3.0 μm or more, or 4.0 μm or more. When the thickness of the microporous membrane is 1.0 μm or more, the membrane strength tends to be further improved. In addition, the thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 80 μm or less, 22 μm or less, or 19 μm or less. When the thickness of the microporous membrane is 500 μm or less, the ion permeability tends to be further improved. The thickness of the microporous membrane can be adjusted by adjusting the stretching ratio, the stretching temperature, etc. The thickness is measured by the method described in the Examples.

[0052] In particular, when a microporous membrane is used as a LIB separator or a constituent material thereof, the membrane thickness is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, and even more preferably 18 μm or less. In this case, the membrane thickness of 25 μm or less tends to further improve permeability. In this case, the lower limit of the membrane thickness may be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more.

[0053] <Method for producing separator for power storage device> Another aspect of the present invention provides a method for producing a separator for an electricity storage device including a microporous membrane. The method for producing a separator for an electricity storage device according to a second embodiment can include a method for producing a microporous membrane, and includes the following steps: (1) A sheet molding process in which pelletized polypropylene (PP), powdered polyethylene (PE), and a plasticizer are extruded into a sheet using an extruder, cooled and solidified, and processed into a sheet-shaped molded product; (2) a stretching step in which the sheet-like molded product is biaxially stretched at an areal magnification of 20 times or more and 250 times or less to form a stretched product; (3) A microporous membrane forming step of extracting a plasticizer from the stretched material to form a microporous membrane; (4) subjecting the microporous membrane to a heat treatment to stretch and relax in the transverse direction (TD) to obtain a heat-treated microporous membrane; and (5) a winding step of winding the heat-treated microporous membrane; Includes.

[0054] In the method for producing a separator for an electricity storage device according to the second embodiment, the PE raw material is made into a powder form, and the PP raw material is made into a pellet form, which are then mixed and extruded to form a film, thereby reducing defects (i.e., the amount of unmelted material) that occur during the mixing and extrusion process of a plurality of raw materials. Unmelted material during the mixing and extrusion process can cause agglomerates, gels, etc. in the finally obtained microporous membrane and the separator containing the same, so a separator including a microporous membrane with reduced defects can achieve the thickness retention characteristic (cycle characteristic) of the separator or the capacity retention characteristic (cycle characteristic) of the electricity storage device when charging and discharging are repeated.

[0055] In the second embodiment, not only can the separator according to the first embodiment described above be obtained, but also the crystal distribution of PE and PP in the microporous film constituting the separator can be optimized as described above, making it easier to accommodate deformation in response to the expansion and contraction of a negative electrode, such as a silicon-containing negative electrode, thereby contributing to the adhesion between the negative electrode and the separator.

[0056] The resin raw material and additives used in the second embodiment can be the same as the PE, PP, PO, and other resins and additives described above for the first embodiment. In addition, like the separator for a power storage device according to the first embodiment, the separator for a power storage device manufactured by the manufacturing method according to the second embodiment preferably has a microporous film containing PE with a crystallite size of 15 nm to 40 nm and PP with a crystallite size of 10 nm to 50 nm, and more preferably, the isotactic pentad fraction (mmmm) of the stereoregular structure of PP is 85.0 mol% to 99.7 mol%. Each step according to the second embodiment will be described below in order.

[0057] [Sheet forming process (1)] In step (1), the pellet-shaped PP raw material, the powder-shaped PE raw material, and the plasticizer are fed to an extruder. As described above, the PE raw material and the PP raw material can be the PE and PP described in the first embodiment at a predetermined mass ratio.

[0058] (Polyethylene (PE) raw material) The PE raw material is preferably in the form of a powder from the viewpoints of improving the yield in the raw material mixing / extrusion steps in the microporous membrane production process and of making it easier to reduce the amount of unmelted material in the obtained microporous membrane, and more preferably 2% by mass to 100% by mass of the powder is used, based on the total mass of PE used.

[0059] The "powder" that is preferable as a PE raw material is one that has a number average particle size (Nd 50 ) is 80μm to 180μm, and the volume average particle size (Vd 50 ) is 120μm to 220μm, and the number particle size distribution (Nd 80 / Nd 20 ) is 1.1 to 4.2, preferably 1.2 to 4.1; 80 / Vd 20 ) is 1.1 to 3.3, preferably 1.15 to 3.2; the crystallite size is within the range of 15 nm to 40 nm; the crystallinity is 30% to 99%, preferably 32% to 98%, more preferably 38% to 97.5%; and the material contains polyethylene. 50 ), volume average particle size (Vd 50 ), number particle size distribution (Nd 80 / Nd 20 ), volume particle size distribution (Vd 80 / Vd 20 ), crystallite size, degree of crystallinity, etc. can be measured by known techniques.

[0060] For example, the number average particle size (Nd 50 ), volume average particle size (Vd 50 ), number particle size distribution (Nd 80 / Nd 20 ), and volume particle size distribution (Vd 80 / Vd 20) can be obtained by measurement using a flow-type image analysis particle size / shape measurement device Particle Insight manufactured by Micromeritics. Also, for example, the crystallite size and crystallinity can be obtained by XRD measurement using an X-ray diffractometer Ultima-IV manufactured by Rigaku Corporation.

[0061] (Polypropylene (PP) raw material) The PP raw material is preferably in the form of pellets, from the viewpoint of improving the yield in the raw material mixing / extrusion steps in the microporous membrane production process and of making it easier to reduce the amount of unmelted material in the obtained microporous membrane, and more preferably 2% by mass to 100% by mass of the pellets are used, based on the total mass of the PP used.

[0062] Pelletized PP can be obtained, for example, by drying polymerized PP powder, extruding it into strands using an extruder, cooling it with water, and cutting it into pellets. In this case, the viscosity average molecular weight (Mv) of the PP powder raw material is preferably 200,000 to 1,000,000, more preferably 250,000 to 900,000, and even more preferably 300,000 to 800,000. The Mv of PP can be calculated according to the following formula by measuring the intrinsic viscosity [η] (dl / g) at 135°C in decalin solvent based on ASTM-D4020. [η]=1.10×10 -4 Mv 0.80

[0063] Here, the "pellets" preferred as the PP raw material are the number average particle size (Nd 50 ), and volume average particle size (Vd 50) and the length of one side is a resinous material having a maximum length of 10 mm or less and a length of 1 mm or more. The shape of the pellets is not particularly limited, and may be, for example, any of a sphere, an oval sphere, and a columnar shape. The pellets are obtained by melt-extruding the raw material using an extruder, arranging it into a strand shape while cooling it with water or air, and continuously cutting it. The dimensions or detailed shape of the pellets can be adjusted, for example, by a strand forming or cutting method.

[0064] (Combination of powdered PE raw material and pelleted PP raw material) By adjusting the PP raw material to the "pellet" form as described above, the swelling rate caused by the plasticizer can be significantly delayed (i.e., it is assumed that the pellet-like PP does not substantially swell). Inside the extruder, it is important not to inhibit the swelling of the powdered PE raw material. Furthermore, from the viewpoint of uniform melting in the melting step after the swelling step, the "pellets" preferred as a PP raw material component are those having a crystallite size larger than that of the "powder" preferred as a PE raw material component and having the crystallite size of the PP explained in the first embodiment.

[0065] In the manufacturing method of pellets, the crystallite size, degree of crystallinity, size and shape of the pellets can be adjusted by the temperature of the extruded resin into strands, the cooling temperature when cutting, or the pulling speed of the strands from the extrusion (melt micro-stretching). 50 ), volume average particle size (Vd 50 ), crystallite size, crystallinity, etc. can be measured by known methods. For example, the number average particle size (Nd 50 ), volume average particle size (Vd 50 ), crystallite size, and crystallinity can be measured by the same method as that of the first embodiment. The size of the pellet can be obtained, for example, by measuring the length of one side with a calibrated caliper.

[0066] Mixing pelletized PP with powdered PE makes it easier to significantly improve the uniformity of swelling of the plasticizer in the extruder. This is believed to be because the swelling rate of pellets can be significantly slower than that of powder. Therefore, pelletized PP does not excessively inhibit the swelling of powdered PE, and such pellets themselves do not basically swell, making them suitable for use in the subsequent melt-kneading process. This makes it easier to uniformly disperse the PP component in the PE component down to the molecular level in the melt-kneading process.

[0067] (Plasticizer) The plasticizer may be a known material as long as it is liquid at a temperature of 20°C to 70°C and has excellent dispersibility for PE or PP. In consideration of the subsequent extraction, the plasticizer used in step (1) is preferably a non-volatile solvent capable of forming a homogeneous solution at or above the melting point of PE or PP. Specific examples of non-volatile solvents include, for example, hydrocarbons such as liquid paraffin, paraffin wax, decane, and decalin; esters such as dioctyl phthalate and dibutyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol. Among them, liquid paraffin is preferred because it has high compatibility with polyethylene, and even when the molten kneaded product is stretched, interfacial peeling between the resin and the plasticizer is unlikely to occur, making it easier to perform uniform stretching.

[0068] (Feeding raw materials to the extruder) Examples of the extruder include a single screw extruder, a twin screw extruder, and a single screw extruder with a screw, among which a twin screw extruder is preferred. In step (1), it is preferable that the raw materials are sheared by a continuous mixer, and it is more preferable that the twin screw extruder is equipped with a continuous mixer.

[0069] The resin raw material and / or plasticizer are supplied to the extruder at a temperature of preferably 25°C to 80°C, more preferably 30°C to 76°C, and even more preferably 30°C to 70°C, from the viewpoint of ensuring appropriate viscosity and ensuring entanglement of polymer chains to an extent that does not cause a decrease in the molecular weight of the resin raw material.

[0070] From the viewpoint of controlling the crystal structure of PE and PP and controlling swelling due to plasticizers, the PE and PP raw materials are processed by the following methods (a) to (c): (a) PP pellets and PE powder are fed into the extruder using separate feeders; (b) PP pellets and PE powder are dry blended and fed into the extruder using one feeder; (c) A method in which PP pellets and PE powder are dry-blended to obtain multiple resin raw materials, and the multiple resin raw materials are each fed into an extruder using a separate feeder; It is preferable that the PE and PP are fed into the extruder by any of the methods described above. Since the control of the crystal structure of PE and PP is important in the mixed state of PE and PP, in the present invention, attention is paid to controlling the dispersion state of PE and PP within the limited residence time in the extruder by utilizing the thermodynamic semi-compatible property of both. From this viewpoint, it has been possible to indirectly control the crystal structure of PE and PP by controlling the size of the PE and PP to be fed (e.g., powder, pellets, etc.). In addition, before PE melts in the extruder, swelling of the plasticizer such as liquid paraffin (LP) is most important for the uniform dispersion of PE itself (e.g., no unmelted material or gel generation). It has been experimentally clarified that the excessive melt of PP mixes with LP and increases the viscosity or non-uniformity of the plasticizer, thereby inhibiting the uniform swelling of PE. From the above viewpoint, it is preferable that the PE and PP raw materials are fed into the extruder by any of the methods (a) to (c) described above.

[0071] In the feeding method (a), the timing of feeding PP and PE into the extruder may be simultaneous, sequential, or continuous, and is preferably simultaneous feeding into a twin-screw extruder. In the feeding methods (b) and (c), the timing of feeding PP and PE into the extruder is simultaneous.

[0072] In the charging method (c), the PP pellets and PE powder may be dry-blended multiple times to obtain multiple resin raw materials, or the PP pellets and PE powder may be dry-blended once to obtain a dry blend product, which may be divided into multiple portions to obtain multiple resin raw materials.

[0073] Among the raw material feeding methods (a) to (c), (a) and (b) are more preferred, and (b) is even more preferred, from the viewpoint of controlling extrusion stability and thereby constructing a uniformly dispersed state of PE and PP, and thereby improving separator thickness retention and / or cell capacity retention after cycle testing.

[0074] Also, the plasticizer can be fed to the twin-screw extruder together with the PE raw material and / or the PP raw material. After feeding the plasticizer to the twin-screw extruder together with the PE raw material and / or the PP raw material, the plasticizer may be additionally fed from the same or different feeder. This type of twin-screw extruder generally has an upper feed port arranged on the upstream side and a middle feed port arranged downstream of the feed port and in the middle of the melt kneading area. Therefore, after feeding the mixed slurry from the upper feed port of the twin-screw extruder, the plasticizer can be additionally fed from the middle feed port of the twin-screw extruder. This makes it easier to adjust the liquid paraffin amount ratio in the resin composition extruded from the twin-screw extruder to a desired ratio, and also makes it easier to adjust the temperature of the resin composition to a desired range. Of course, the first component or the second component can also be fed from the middle feed port.

[0075] The mixed slurry may be prepared using a continuous mixer. The lower limit of the set temperature of the continuous mixer is preferably 25°C or more, more preferably 30°C or more, from the viewpoint of maximally swelling the PE raw material and the plasticizer, and the upper limit is preferably 68°C or less, more preferably 67°C or less, 66°C or less, or 65°C or less, from the viewpoint of melting the resin raw material during mixing.

[0076] The shear rate of the continuous mixer was set to 100 s from the viewpoint of uniformly contacting the resin raw material with the plasticizer and obtaining a dispersion. -1 ~400,000 seconds -1 and preferably 120 seconds -1 ~398,000 seconds -1 , more preferably 1,000 seconds -1 ~100,000 seconds -1 It is.

[0077] The residence time in the continuous mixer is from 1.0 seconds to 60 seconds, preferably from 2.0 seconds to 58 seconds, and more preferably from 2.0 seconds to 56 seconds, from the viewpoint of ensuring dispersion of the resin raw material in the plasticizer.

[0078] (Melting and kneading) In step (1), the resin raw material and the plasticizer are melt-kneaded in a twin-screw extruder to produce a resin composition. In the second embodiment, the type of device used for melt-kneading, the time, and other conditions are not limited as long as the uniform swelling of the resin raw material with respect to the plasticizer is ensured. If desired, PO resins other than PE and PP, resin raw materials other than PO, and known additives, such as dehydration condensation catalysts, metal soaps such as calcium stearate or zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, color pigments, and the like, may also be added to the twin-screw extruder.

[0079] (cooling and solidifying, sheet forming) In step (1), the molten kneaded product is molded into a sheet. Examples of methods for producing a sheet-shaped molded product include extruding the molten kneaded product into a sheet through a T-die or the like, contacting it with a heat conductor, and cooling it to a temperature sufficiently lower than the crystallization temperature of the resin component to solidify it. Examples of heat conductors used for cooling and solidifying include metal, water, air, plasticizers, and the like. Among these, it is preferable to use a metal roll because of its high thermal conductivity. In addition, when the extruded kneaded product is brought into contact with a metal roll, it is more preferable to sandwich it between at least a pair of rolls, because this further increases the efficiency of thermal conduction, and the sheet is oriented to increase the film strength and the surface smoothness of the sheet also tends to be improved. When the resin composition is extruded into a sheet from a T-die, the die lip distance is preferably 200 μm or more and 3,000 μm or less, and more preferably 500 μm or more and 2,500 μm or less. When the die lip distance is 200 μm or more, the occurrence of scum is reduced, and the influence on the film quality such as streaks or defects is small, and the risk of film breakage in the subsequent stretching process can be reduced. On the other hand, when the die lip distance is 3,000 μm or less, the cooling speed is fast, and cooling unevenness can be prevented, and the thickness stability of the sheet can be maintained. The extruded sheet-like molded body may also be rolled.

[0080] [Stretching process (2)] In step (2), the sheet-like molded product obtained in step (1) is stretched at an areal stretching ratio of 20 to 250 times. When the areal stretching ratio is 20 times or more, the resulting microporous film tends to have sufficient strength, while when the areal stretching ratio is 250 times or less, film breakage tends to be prevented and high productivity tends to be obtained. Step (2) may be performed before the porous body formation step (3), or may be performed on the porous body after step (3). Furthermore, step (2) may be performed before or after the extraction of the plasticizer from the sheet-like molded product.

[0081] As the stretching process, biaxial stretching is preferred over uniaxial stretching from the viewpoint of reducing the film thickness distribution and air permeability distribution in the transverse direction (TD). By simultaneously stretching the sheet in two axial directions, the number of times the sheet-like molded body is cooled and heated repeatedly during the film-forming process is reduced, and the distribution in the transverse direction is improved. Examples of the biaxial stretching method include simultaneous biaxial stretching, sequential biaxial stretching, multi-stage stretching, and multiple stretching. From the viewpoint of improving the puncture strength and uniformity of stretching, simultaneous biaxial stretching is preferred, and from the viewpoint of easy control of the plane orientation, sequential biaxial stretching is preferred.

[0082] In this specification, simultaneous biaxial stretching refers to a stretching method in which stretching in MD (machine direction of continuous microporous membrane molding) and stretching in TD (direction crossing the MD of the microporous membrane at an angle of 90°) are performed simultaneously, and the stretching ratios in each direction may be different. Sequential biaxial stretching refers to a stretching method in which stretching in MD and TD is performed independently, and while stretching is performed in MD or TD, the other direction is in an unconstrained state or fixed at a fixed length.

[0083] The areal stretch ratio is preferably in the range of 20 to 200, more preferably in the range of 25 to 170, and even more preferably in the range of 30 to 150. The stretch ratios in each axial direction are preferably in the range of 2 to 15 in MD and 2 to 15 in TD, more preferably in the range of 3 to 12 in MD and 3 to 12 in TD, and even more preferably in the range of 5 to 10 in MD and 5 to 10 in TD.

[0084] The stretching temperature is preferably 90°C to 150°C, more preferably 100°C to 140°C, and even more preferably 110°C to 130°C, from the viewpoints of the meltability and film-forming properties of the PE / PP raw material.

[0085] [Microporous membrane formation process (3)] In step (3), the plasticizer is extracted from the resin composition formed in (1) or from the stretched product formed in step (2) to form a microporous membrane. An example of a method for extracting the plasticizer is a method in which the stretched product is immersed in an extraction solvent to extract the plasticizer and then dried. The extraction method may be either a batch method or a continuous method. In order to suppress shrinkage of the microporous membrane, it is preferable to restrain the ends of the sheet-like molded product during a series of steps of immersion and drying. In addition, the amount of plasticizer remaining in the microporous membrane is preferably less than 1% by mass with respect to the mass of the entire microporous membrane. After step (3), the plasticizer may be recovered by an operation such as distillation and reused.

[0086] As the extraction solvent, it is preferable to use one that is a poor solvent for PE and PP resins, a good solvent for plasticizers, and has a boiling point lower than the melting points of PE and PP resins. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as methylene chloride and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. These extraction solvents may be recovered and reused by operations such as distillation.

[0087] [Heat treatment process (4)] In step (4), for example, the microporous membrane obtained in step (3) is heat-treated at a temperature not exceeding its melting point, and then the microporous membrane is stretched to produce a heat-treated microporous membrane.

[0088] The microporous membrane is heat-treated for the purpose of heat setting in order to suppress shrinkage. Examples of the heat treatment method include a stretching operation performed in a predetermined atmosphere, at a predetermined temperature, and at a predetermined stretch ratio for the purpose of adjusting physical properties, and / or a relaxation operation performed in a predetermined atmosphere, at a predetermined temperature, and at a predetermined relaxation ratio for the purpose of reducing stretching stress. The relaxation operation may be performed after the stretching operation. These heat treatments can be performed using a tenter or roll stretching machine.

[0089] From the viewpoint of increasing the strength and porosity of the microporous membrane, the stretching operation is preferably performed at 1.1 times or more, more preferably 1.2 times or more, in the MD and / or TD of the membrane. The upper limit of the stretching ratio during heat setting is preferably 3.0 times or less, more preferably 2.5 times or less, in both MD and TD.

[0090] The relaxation operation is a shrinking operation in the MD and / or TD of the membrane. The relaxation rate is a value obtained by dividing the membrane dimension after the relaxation operation by the membrane dimension before the relaxation operation. When both the MD and TD are relaxed, the relaxation rate is a value obtained by multiplying the relaxation rate in MD and the relaxation rate in TD. The relaxation rate is preferably 0.99 or less, more preferably 0.95 or less. From the viewpoint of membrane quality, the relaxation rate is preferably 0.5 or more. The relaxation operation may be performed in both the MD and TD, or in only one of the MD and TD.

[0091] The temperature of the heat treatment including the stretching or relaxation operation is preferably within the range of 100°C to 170°C from the viewpoint of the melting point (hereinafter also referred to as "Tm") of the PE and PP resins. The temperatures of the stretching and relaxation operations within the above range are preferable from the viewpoint of the balance between the reduction of the thermal shrinkage rate and the porosity. The lower limit of the heat treatment temperature is more preferably 110°C or more, even more preferably 115°C or more, and the upper limit is more preferably 160°C or less, even more preferably 150°C or less, and even more preferably 140°C or less.

[0092] [Winding process (5)] In step (5), the microporous membrane heat-treated in the heat treatment step (4) or the microporous membrane produced by the second embodiment can be wound into a roll, for example, by a winder. The resulting roll can be stored until the microporous membrane is used to produce a separator for an electricity storage device.

[0093] [Other processes] The obtained microporous membrane or roll can be cut with a slitter from the viewpoints of handling and storage stability. The microporous membrane may be subjected to post-treatment such as hydrophilization treatment with a surfactant or crosslinking treatment with ionizing radiation. The microporous membrane obtained by steps (1) to (5) may be used as a single-layer separator, or multiple microporous membranes may be laminated, the microporous membrane may be laminated with another membrane, a functional layer may be provided on the microporous membrane, or the microporous membrane may be coated.

[0094] <Electricity storage device> An electric storage device according to another embodiment of the present invention includes a positive electrode, a negative electrode, and a separator including the microporous membrane described above. Specific examples of the electric storage device include lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel hydrogen batteries, nickel cadmium batteries, electric double layer capacitors, lithium ion capacitors, redox flow batteries, lithium sulfur batteries, lithium air batteries, and zinc air batteries. Among these, from the viewpoint of practicality, lithium secondary batteries, lithium ion secondary batteries (LIBs), nickel hydrogen batteries, or lithium ion capacitors are preferred, and lithium ion secondary batteries are more preferred. In addition, the batteries listed above preferably contain an electrolyte from the viewpoints of ion conductivity, charge and discharge characteristics, and the like.

[0095] The electrolyte in the battery may contain water, and the water contained in the system after the battery is produced may be water contained in the electrolyte, or water carried in from components such as electrodes or separators. The electrolyte may contain a non-aqueous solvent. Examples of the solvent contained in the non-aqueous solvent of the present embodiment include alcohols such as methanol and ethanol; aprotic solvents, etc. Among them, aprotic solvents are preferred as the non-aqueous solvent.

[0096] Examples of aprotic solvents include cyclic carbonates, fluoroethylene carbonates, lactones, organic compounds having sulfur atoms, chain fluorinated carbonates, cyclic ethers, mononitriles, alkoxy group-substituted nitriles, dinitriles, cyclic nitriles, short-chain fatty acid esters, chain ethers, fluorinated ethers, ketones, and compounds in which some or all of the H atoms of the above aprotic solvents have been substituted with halogen atoms.

[0097] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, trans-2,3-butylene carbonate, cis-2,3-butylene carbonate, 1,2-pentylene carbonate, trans-2,3-pentylene carbonate, cis-2,3-pentylene carbonate, vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate.

[0098] Examples of fluoroethylene carbonate include 4-fluoro-1,3-dioxolan-2-one, 4,4-difluoro-1,3-dioxolan-2-one, cis-4,5-difluoro-1,3-dioxolan-2-one, trans-4,5-difluoro-1,3-dioxolan-2-one, 4,4,5-trifluoro-1,3-dioxolan-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolan-2-one, and 4,4,5-trifluoro-5-methyl-1,3-dioxolan-2-one.

[0099] Examples of lactones include γ-butyrolactone, α-methyl-γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone.

[0100] Examples of organic compounds having a sulfur atom include ethylene sulfite, propylene sulfite, butylene sulfite, pentene sulfite, sulfolane, 3-sulfolene, 3-methylsulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propene 1,3-sultone, dimethyl sulfoxide, tetramethylene sulfoxide, and ethylene glycol sulfite.

[0101] Examples of the chain carbonate include ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, and ethyl propyl carbonate.

[0102] Examples of cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, and 1,3-dioxane.

[0103] Examples of mononitriles include acetonitrile, propionitrile, butyronitrile, valeronitrile, benzonitrile, and acrylonitrile.

[0104] Examples of alkoxy-substituted nitriles include methoxyacetonitrile and 3-methoxypropionitrile.

[0105] Examples of dinitriles include malononitrile, succinonitrile, methylsuccinonitrile, glutaronitrile, 2-methylglutaronitrile, adiponitrile, 1,4-dicyanoheptane, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 2,6-dicyanoheptane, 1,8-dicyanooctane, 2,7-dicyanooctane, 1,9-dicyanonane, 2,8-dicyanononane, 1,10-dicyanodecane, 1,6-dicyanodecane, 2,4-dimethylglutaronitrile, and ethylene glycol bis(propionitrile) ether.

[0106] Examples of cyclic nitriles include benzonitrile.

[0107] Examples of short-chain fatty acid esters include methyl acetate, methyl propionate, methyl isobutyrate, methyl butyrate, methyl isovalerate, methyl valerate, methyl pivalate, methyl hydroangelate, methyl caproate, ethyl acetate, ethyl propionate, ethyl isobutyrate, ethyl butyrate, ethyl isovalerate, ethyl valerate, ethyl pivalate, ethyl hydroangelate, ethyl caproate, propyl acetate, propyl propionate, propyl isobutyrate, propyl butyrate, propyl isovalerate, propyl valerate, propyl pivalate, propyl hydroangelate, propyl caproate, isopropyl acetate, isopropyl propionate, isopropyl isobutyrate, isopropyl butyrate, isopropyl isovalerate, isopropyl valerate, and isopropyl pivalate. , isopropyl hydroangelate, isopropyl caproate, butyl acetate, butyl propionate, butyl isobutyrate, butyl butyrate, butyl isovalerate, butyl valerate, butyl pivalate, butyl hydroangelate, butyl caproate, isobutyl acetate, isobutyl propionate, isobutyl isobutyrate, isobutyl butyrate, isobutyl isovalerate, isobutyl valerate, isobutyl pivalate, isobutyl hydroangelate, isobutyl caproate, tert-butyl acetate, tert-butyl propionate, tert-butyl isobutyrate, tert-butyl butyrate, tert-butyl isovalerate, tert-butyl valerate, tert-butyl pivalate, tert-butyl hydroangelate, and tert-butyl caproate.

[0108] Examples of chain ethers include dimethoxyethane, diethyl ether, 1,3-dioxolane, diglyme, triglyme, and tetraglyme. The fluorinated ethers include, for example, those represented by the general formula Rf aa -OR bb (In the formula, Rf aa is an alkyl group containing a fluorine atom, and R bb is an organic group which may contain a fluorine atom).

[0109] Examples of ketones include acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0110] Examples of the above-mentioned aprotic solvent compounds in which some or all of the H atoms have been substituted with halogen atoms include compounds in which the halogen atoms are fluorine.

[0111] Here, examples of fluorinated chain carbonates include methyl trifluoroethyl carbonate, trifluorodimethyl carbonate, trifluorodiethyl carbonate, trifluoroethylmethyl carbonate, methyl 2,2-difluoroethyl carbonate, methyl 2,2,2-trifluoroethyl carbonate, and methyl 2,2,3,3-tetrafluoropropyl carbonate. The above-mentioned fluorinated chain carbonates are represented by the following general formula: R cc -OC(O)OR dd {where, R cc and R dd is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and the formula CH2Rf ee (In the formula, Rf ee is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom), and R cc and / or R dd contains at least one fluorine atom. It can be expressed as:

[0112] Examples of fluorinated short-chain fatty acid esters include fluorinated short-chain fatty acid esters such as 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, and 2,2,3,3-tetrafluoropropyl acetate. Fluorinated short-chain fatty acid esters are represented by the following general formula: R ff -C(O)OR gg {where, R ffis CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, CF3CF2H, CFH2, CF2H, CF2Rf hh , CFHRf hh , and CH2Rf ii and R is at least one selected from the group consisting of gg is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and CH2Rf ii Rf is at least one selected from the group consisting of hh is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom may be substituted with at least one fluorine atom, and Rf ii is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom, and R ff and / or R gg contains at least one fluorine atom, and R ff If is CF2H, R gg can be expressed as {is not CH3}.

[0113] <lib> The LIB is a storage battery that uses a lithium transition metal oxide such as lithium cobalt oxide or lithium cobalt composite oxide as the positive electrode, a carbon material such as graphite or graphite or a silicon-containing material as the negative electrode, and an organic solvent containing a lithium salt such as LiPF6 as the electrolyte. When the LIB is charged and discharged, ionized Li moves back and forth between the electrodes. In addition, since it is necessary for the ionized Li to move relatively quickly between the electrodes while suppressing contact between the electrodes, a separator is disposed between the electrodes. From the viewpoint of closely adhering the separator according to the first embodiment or the separator manufactured according to the second embodiment to the negative electrode without any gap, the negative electrode of the LIB is preferably a silicon-containing negative electrode.

[0114] Unless otherwise specified, the condition values, physical property values, characteristic values, etc. described above are measured according to the methods described in the Examples section below. When the separator includes one microporous membrane and another layer, is a coating membrane, or includes multiple microporous membranes, one microporous membrane is removed from the separator or the coating portion is removed from the separator to measure or evaluate the properties of the microporous membrane. EXAMPLES

[0115] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to the following examples without departing from the gist of the present invention. The physical properties in the examples were measured by the following methods.

[0116] <Weight average molecular weight (Mw), number average molecular weight (Mn)> A calibration curve was created by measuring standard polystyrene under the following conditions using a Waters ALC / GPC 150C (trademark). Chromatograms were also measured for the following polymers under the same conditions, and the weight-average molecular weight and number-average molecular weight of each polymer were calculated based on the calibration curve by the following method. Column: Tosoh GMH6-HT (trademark) x 2 + GMH6-HTL (trademark) x 2 Mobile phase: o-dichlorobenzene Detector: Differential refractometer Flow rate: 1.0ml / min Column temperature: 140℃ Sample concentration: 0.1wt% (Weight average molecular weight and number average molecular weight of polyethylene and polypropylene) Each molecular weight component in the obtained calibration curve was multiplied by 0.43 (Q factor of polyethylene / Q factor of polystyrene=17.7 / 41.3) or 0.64 (Q factor of polypropylene / Q factor of polystyrene=26.4 / 41.3) to obtain a polyethylene-equivalent or polypropylene-equivalent molecular weight distribution curve, and the weight average molecular weight and number average molecular weight were calculated.

[0117] <mmmm pentad fraction related to stereoregular structure> The isotactic pentad fraction (mmmm) in the polypropylene component is 13 It is determined as the (mmmm) peak fraction among all absorption peaks in the methyl carbon region measured by C-NMR. The assignment of signals in the methyl group region, including isotactic pentads, is in accordance with A. Zambellietal. (Macromolecules 8, 687 (1975). Specifically, the mmmm pentad fraction for the stereoregular structure of the raw material and the PP contained in the microporous membrane is measured as follows. <mmmm pentad fraction related to stereoregular structure of PP contained in raw material and microporous membrane> The sample was dissolved in o-dichlorobenzene-D4 at 130°C or higher to a concentration of 10% by weight. 13 C-NMR measurements were performed under the following conditions: Equipment:Bruker Avance NEO 600 Pulse program: zgpg30 Pulse waiting time: 5sec Sample tube diameter: 5mmΦ Measurement temperature: 130℃ 13 In the C-NMR spectrum, the mmmm pentad was assigned to 21.8 ppm, and the peaks in the methyl region from 18 ppm to 22 ppm were assigned to mmmm, mmmr, rmmr, mmrr, rmrr, rmrm, mmrm, rrrr, rrrm, and mrrm. The integral value of the mmmm pentad was divided by the sum of the integral values ​​of these peaks to calculate the mmmm pentad fraction. The chemical shifts of each three-dimensional structure are as follows: mmmm 21.8ppm, mmmr 21.6ppm, rmr 21.3ppm, mmrr 21.0ppm, mmrm+rmrr 20.8ppm, rmrm 20.6ppm, rrrr 20.3ppm, rrrm 20.2ppm, mrrm 19.9ppm It is.

[0118] <Film thickness (μm)> The thickness of the separator sample was measured using a micro thickness gauge (Type KBM, manufactured by Toyo Seiki) at room temperature of 23°C and humidity of 40%. The measurement was performed by applying a load of 44gf using a terminal with a terminal diameter of 5mmφ.

[0119] <Porosity (%)> A 10 cm x 10 cm square sample was cut from the microporous membrane and its volume (cm 3 ) and mass (g), and then calculate the density (g / cm 3 ) the porosity was calculated using the following equation. Porosity (%) = (volume-mass / density) / volume x 100

[0120] <Air permeability (sec / 100cm 3 )> In accordance with JIS P-8117, the air resistance of the polyolefin microporous membrane was measured in an atmosphere of 23°C and 40% humidity using a Gurley air permeability meter, G-B2 (trademark), manufactured by Toyo Seiki Co., Ltd., and this was taken as the air permeability.

[0121] <Crystal structure analysis> The crystallite size of polyolefin (eg, PE, PP, etc.) contained in the separator or in the microporous film contained in the separator may be measured by either reflection X-ray diffraction or transmission wide-angle X-ray scattering.

[0122] (Wide-angle transmission X-ray scattering measurement) The crystallite size of polyolefin (e.g., PE, PP, etc.) contained in the separator or in the microporous membrane contained in the separator was measured using a Rigaku Corporation transmission type X-ray scattering device NANOPIX. The sample was irradiated with Cu-Kα radiation, and scattering was detected using a semiconductor detector Hypix-6000. The measurement was performed under the following conditions: sample-detector distance 86 mm, output 40 kV, 30 mA. A point focus optical system was used, and the measurement was performed under the following conditions: 1st slit: φ=0.55 mm, 2nd slit: open, Guard slit: φ=0.35 mm.

[0123] ·Crystallite size (nm) and crystallinity in wide-angle transmission X-ray scattering measurements In the case of transmission wide-angle X-ray scattering measurement, in the X-ray scattering pattern obtained by the two-dimensional detector, when the position where the X-ray irradiated to the sample travels straight through the sample, passes through the sample, and reaches the two-dimensional detector is the center, the scattering intensity at the same distance from the center corresponds to the same scattering angle. Therefore, by calculating the intensity average at each scattering angle for the measured X-ray scattering pattern (circular average), a one-dimensional scattering intensity profile for the scattering angle 2θ can be obtained. In the range of 2θ=10.0° to 2θ=29.0° of the obtained one-dimensional profile, a process was performed to separate the diffraction peaks into six peaks: the orthorhombic (110) diffraction peak of polyethylene, the orthorhombic (200) diffraction peak of polypropylene, the α-crystal (110) diffraction peak of polypropylene, the α-crystal (040) diffraction peak of polypropylene, the α-crystal (130) diffraction peak of polypropylene, and the amorphous peak of polyethylene. A baseline was drawn connecting 2θ=10.0° to 2θ=29.0° with a straight line, and the (110) and (200) diffraction peaks of polyethylene were approximated by a Voigt function, and the (110), (040), and (130) diffraction peaks of polypropylene and the amorphous peak of polyethylene were approximated by a Gaussian function. The peak position of the amorphous peak was fixed at 2θ=19.6° and the full width at half maximum was fixed at 6.3°, and the peak position and full width at half maximum of the crystalline peak were not fixed in particular when performing peak separation. The crystallite size was calculated according to Scherrer's formula (below) from the full width at half maximum of the (110) diffraction peak of polyethylene and the (110) diffraction peak of polypropylene calculated by peak separation. The degree of crystallinity can be obtained as a percentage value obtained by dividing the sum of the separated crystalline and amorphous peaks by the area of ​​the crystalline peak. D = Kλ / (βcosθ) D: Crystallite size (nm) K: 0.9 (constant) λ: wavelength of X-rays (nm) β:(β1 2 -β2 2 ) 0.5 β1: Full width at half maximum (rad) of the (hkl) peak calculated as a result of peak separation β2: Full width at half maximum of the incident beam divergence (rad) θ: Bragg angle

[0124] (Reflection X-ray diffraction measurement) ·Polyolefin crystallite size (nm) and crystallinity measured by reflection X-ray diffraction XRD measurements were performed on polyolefins (e.g., PE, PP, etc.) contained in separators using a Rigaku Ultima-IV X-ray diffractometer. Cu-Kα rays were incident on the sample, and diffracted light was detected using a Rigaku D / tex Ultra detector. KRD measurements were performed under conditions of a sample-detector distance of 285 mm, an excitation voltage of 40 kV, and a current of 40 mA. A focused optical system was used as the optical system, and measurements were performed under slit conditions of DS=1 / 2°, SS=open, and vertical slit=10 mm.

[0125] Analysis of reflection X-ray diffraction measurements In the case of polyethylene The range of the obtained XRD profile from 2θ=9.7° to 2θ=29.0° was separated into three peaks, the orthorhombic (110) diffraction peak, the orthorhombic (200) diffraction peak, and the amorphous peak. The crystallite size was calculated from the full width at half maximum of the (110) diffraction peak according to Scherrer's formula (see below). The (110) diffraction peak and the (200) diffraction peak were approximated by a Voigt function, and the amorphous peak was approximated by a Gaussian function. The peak position of the amorphous peak was fixed at 2θ=19.6°, and the full width at half maximum was fixed at 6.3°, while the peak position and full width at half maximum of the crystalline peak were not fixed. The crystallite size was calculated from the full width at half maximum of the (110) diffraction peak calculated by peak separation according to Scherrer's formula (see below). The degree of crystallinity can be obtained as a percentage by dividing the area of ​​the crystalline peak by the sum of the separated crystalline and amorphous peaks.

[0126] In the case of polypropylene In the range of 2θ=6° to 2θ=31° of the obtained XRD profile, the diffraction peaks derived from crystals were separated into five, namely, (110), (040), (130), (111) and (13-1) / (041) planes of α crystals (monocrystalline crystals), and the diffraction peaks derived from amorphous crystals were separated into two. The separated diffraction peaks derived from crystals and amorphous crystals were approximated by Gaussian functions. The two amorphous peaks were fixed as follows and peak separation was performed. Amorphous peak 1 was fixed at 2θ=14.9° and full width at half maximum 4.7°, and amorphous peak 2 was fixed at 2θ=19.18° and full width at half maximum 7.0°. The crystallite size was calculated from the full width at half maximum of the (110) plane diffraction peak obtained by peak separation according to the Scherrer formula (below). The degree of crystallinity can be taken as a percentage of the sum of the separate crystalline and amorphous peaks divided by the area of ​​the crystalline peak. D(110) = Kλ / (βcosθ) D(110): Crystallite size (nm) K: 0.9 (constant) λ: wavelength of X-rays (nm) β:(β1 2 -β2 2 ) 0.5 β1: Full width at half maximum (rad) of the (hkl) peak calculated as a result of peak separation β2: Full width at half maximum of the incident beam divergence (rad) θ: Bragg angle

[0127] < Unmelted material in separator (pieces / 1000m 2 )> The amount of unmelted material in the separator is quantified by a region having an area of ​​100 μm length × 100 μm width or more and through which light does not pass, when the separator obtained through the film-forming process of the examples and comparative examples is observed with a transmission optical microscope. 2 The number of resin aggregates per unit area was measured.

[0128] <Cycle test (%) Test method 1> A positive electrode, a negative electrode, and a non-aqueous electrolyte solution were prepared by the following steps a to c.

[0129] a. Preparation of the positive electrode The positive electrode active material was nickel, manganese, and cobalt composite oxide (NMC) (Ni:Mn:Co=1:1:1 (element ratio), density 4.70 g / cm 3 ) at 90.4 mass%, and graphite powder (KS6) (density 2.26 g / cm3) as a conductive additive. 3 , number average particle diameter 6.5 μm) at 1.6 mass%, and acetylene black powder (AB) (density 1.95 g / cm 3 , number average particle diameter 48 nm) at 3.8 mass%, and polyvinylidene fluoride (PVDF) (density 1.75 g / cm3) as a binder. 3 ) were mixed at a ratio of 4.2 mass%, and dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. This slurry was applied to one side of an aluminum foil having a thickness of 20 μm, which serves as a positive electrode current collector, using a die coater, and dried at 130° C. for 3 minutes, and then compression molded using a roll press to prepare a positive electrode. The amount of the positive electrode active material applied at this time was 109 g / m 2 It was.

[0130] b. Preparation of the negative electrode According to the method described in Non-Patent Document 3, a graphene negative electrode containing 40% silicon was prepared, and supported to a thickness of 3.6 μm on a copper foil having a thickness of 12 μm as a negative electrode current collector to produce a negative electrode.

[0131] c. Preparation of non-aqueous electrolyte A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L.

[0132] d. Battery construction The thickness of the microporous film used as the separator was measured according to the method described in the above item <Film thickness (μm)>. A laminated secondary battery with a size of 100 mm x 60 mm and a capacity of 3 Ah was produced by charging for 3 hours at a constant current constant voltage (CCCV) under conditions of a current value of 1 A (0.3 C) and an end battery voltage of 4.2 V using the positive electrode, negative electrode, and nonaqueous electrolyte obtained in the above a to c, and a separator (the separator of the Example or the separator of the Comparative Example).

[0133] e. Cycle test, thickness retention rate (%) and capacity retention rate (%) (e1) Pretreatment The battery prepared in d. above was charged at a constant current of 1 / 3C to a voltage of 4.2V, then charged at a constant voltage of 4.2V for 8 hours, and then discharged at a current of 1 / 3C to an end voltage of 3.0V. Next, it was charged at a constant current of 1C to a voltage of 4.2V, then charged at a constant voltage of 4.2V for 3 hours, and then discharged at a current of 1C to an end voltage of 3.0V. Finally, it was charged at a constant current of 1C to 4.2V, and then charged at a constant voltage of 4.2V for 3 hours. Note that 1C refers to the current value at which the battery's reference capacity is discharged in 1 hour.

[0134] (e2) Cycle test The battery that had been pretreated in the above (e1) was discharged at a discharge current of 1 C to a discharge end voltage of 3 V under a temperature condition of 25° C., and then charged at a charge current of 1 C to a charge end voltage of 4.2 V. This constituted one cycle, and charging and discharging were repeated. The capacity retention rate after 1000 cycles relative to the initial capacity (capacity in the first cycle) was calculated in percentage using the following formula. Evaluation result (%) = 100 x (retained capacity after 1000 cycles / initial capacity)

[0135] In addition, the separator was removed from the battery after 100 cycles, and its thickness was measured according to the method described above in <Film thickness (μm)>. The thickness retention rate of the separator after 100 cycles was calculated in % according to the following formula. Evaluation result (%) = 100 x (separator thickness after 100 cycles / separator thickness measured in d. above) The thickness of the removed separator was measured at 10 random points, and the average value was used.

[0136] <Cycle test (%) Test method 2> (Battery Construction) a. Preparation of the positive electrode LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O2, carbon black as a conductive assistant, and polyvinylidene fluoride solution as a binder were mixed in a solid content mass ratio of 91:5:4, and N-methyl-2-pyrrolidone was added as a dispersion solvent so that the solid content was 68 mass%, and further mixed to prepare a slurry solution. This slurry solution was applied to both sides of an aluminum foil with a thickness of 15 μm so that part of the aluminum foil was exposed, and then the solvent was dried and removed, and the coating amount was set to 175 g / m per side. 2 Furthermore, the density of the positive electrode mixture was 2.8 g / cm 3 The coated area was then cut to a size of 30 mm×50 mm including the exposed aluminum foil area to obtain a positive electrode.

[0137] b. Preparation of the negative electrode As the negative electrode active material, artificial graphite / silicon particles (Elkem, Silgrain e-Si 408) = 1:1 (mass ratio) and as the binder, styrene butadiene rubber and carboxymethyl cellulose aqueous solution were mixed in a solid content mass ratio of negative electrode active material:styrene butadiene rubber:carboxymethyl cellulose = 96.4:1.9:1.7, water was added as a dispersion solvent so that the solid content was 50 mass%, and further mixed to prepare a slurry solution. This slurry solution was applied to both sides of a 10 μm thick copper foil so that part of the copper foil was exposed, and then the solvent was dried and removed, and the coating amount was 86 g / m per side. 2 Furthermore, the density of the negative electrode mixture was 1.45 g / cm 3 The coated area was then cut to a size of 32 mm×52 mm including the exposed copper foil area to obtain a negative electrode.

[0138] c. Preparation of non-aqueous electrolyte LiPF6 was dissolved as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate = 1:2 (volume ratio) to a concentration of 1.0 mol / L, and vinylene carbonate was further added to the solution to a concentration of 1.0 wt % to prepare a non-aqueous electrolyte solution.

[0139] d. Battery assembly A long separator with a width of 55 mm was folded zigzag so that the active material surfaces of the positive and negative electrodes faced each other and were interposed between the positive and negative electrodes, to form a laminate consisting of 15 double-sided negative electrodes and 14 double-sided positive electrodes. Aluminum lead pieces with sealant were welded to the exposed parts of the 14 positive aluminum foils of this laminate, and nickel lead pieces with sealant were welded to the exposed parts of the 15 negative copper foils, and then the laminate was inserted into an aluminum laminate exterior body, and the sides where the positive and negative lead pieces were exposed and the other two sides, a total of three sides, were laminated and sealed. Next, the nonaqueous electrolyte was injected into the exterior body, and the opening was then sealed to produce a 28-opposed laminate type battery. The resulting battery was left at room temperature for one day, and then charged at a constant current of 330 mA (0.3 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and then charged at a constant voltage to maintain 4.2 V. This method was used for the first charging after the battery was fabricated, for a total of 8 hours. The battery was then discharged at a current value of 330 mA (0.3 C) down to a battery voltage of 3.0 V.

[0140] (Cycle characteristic evaluation) The battery obtained in "d. Battery assembly" above was charged and discharged 1000 cycles in an atmosphere of 25°C. The battery was charged for a total of 3 hours by charging at a constant current of 1A (1.0C) up to a battery voltage of 4.2V, and then constant voltage charging to maintain 4.2V after reaching that voltage. The battery was discharged at a current value of 1A (1.0C) down to a battery voltage of 3.0V. The capacity retention rate was calculated from the discharge capacity at the 1000th cycle and the discharge capacity at the 1st cycle. A high capacity retention rate was evaluated as having good cycle characteristics. Evaluation result (%) = 100 x (retained capacity after 1000 cycles / initial capacity)

[0141] In addition, the separator was removed from the battery after 100 cycles, and its thickness was measured according to the method described above in <Film thickness (μm)>. The thickness retention rate of the separator after 100 cycles was calculated in % according to the following formula. Evaluation result (%) = 100 x (separator thickness after 100 cycles / separator thickness measured in d. above) The thickness of the removed separator was measured at 10 random points, and the average value was used.

[0142] <Polyethylene (PE) raw material> Polyethylene (PE) shown in Table 1 was prepared.

[0143] <Polypropylene (PP) raw material used> Polypropylene (PP) shown in Table 2 or Table 3 was prepared.

[0144] [Example 1] The PE1 powder and the PP1 pellets were fed to a twin-screw extruder equipped with a manifold (T-die) with a die lip spacing of 1500 μm according to the feeding method (a) in the mass ratio shown in Table 4, and melt-mixed. During the melt-mixing, liquid paraffin (dynamic viscosity at 37.78° C.: 7.59×10 -5 m 2 / s) was fed to a twin-screw extruder by an injection nozzle, and further kneaded to extrude a resin composition. At this time, liquid paraffin was further injected from the middle stage of the extrusion (middle stage feed port of the twin-screw extruder) so that the ratio of liquid paraffin in the resin composition extruded from the twin-screw extruder was 70% by mass and the temperature of the resin composition was 220°C. Next, the extruded resin composition was extruded onto a cooling roll whose surface temperature was controlled to 25°C, and cast to obtain a sheet-like molded product.

[0145] Next, the sheet-like molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were as shown in Table 4, and the stretching areal ratio was 55 times. The porosity, air permeability, thickness, etc. were adjusted by appropriately adjusting the stretching temperature, heating air volume, etc. The biaxial stretching temperature was set to 126°C.

[0146] Next, the stretched product was immersed in dichloromethane to extract the liquid paraffin from the stretched product, thereby forming a microporous membrane.

[0147] Next, the microporous membrane was introduced into a TD tenter for heat setting, heat set (HS) at 129°C, stretched at a TD stretch ratio of 2.0 times, and then relaxed to 0.9 times in the TD direction (i.e., stretched 2.0 times in the TD direction compared to before heat setting, and then relaxed to 1.8 times). The heat-treated microporous membrane was evaluated as above. Then, the microporous membrane was used as a separator to perform the separator evaluation and battery evaluation as above. The evaluation results are shown in Table 4.

[0148] [Examples 2 to 20 and Comparative Examples 1 to 3] Microporous membranes were produced and evaluated in the same manner as in Example 1, except that the raw material composition, raw material charging method, or stretching ratio in the stretching step was changed as shown in Tables 4 to 6. The evaluation results of the obtained microporous membranes, separators, and batteries are shown in Tables 4 to 6.

[0149] [Table 1]

[0150] [Table 2]

[0151] [Table 3]

[0152] [Table 4]

[0153] [Table 5]

[0154] [Table 6]

[0155] (Explanation of abbreviations in Tables 4 to 6) Raw material feeding method (a): PE and PP are fed into the extruder from separate feeders. Raw material feeding method (b): A dry blend of PE and PP is fed into the extruder from a single feeder. Raw material feeding method (c) Multiple resin raw materials are obtained by dry blending PE and PP, and the resulting multiple resin raw materials are fed into the extruder from individual feeders.< / lib>

Claims

1. The following steps: (1) a sheet molding step in which pelletized polypropylene, powdered polyethylene, and a plasticizer are extruded into a sheet using an extruder, cooled and solidified, and processed into a sheet-like molded product; (2) a stretching step of stretching the sheet-like molded body at an areal stretching ratio of 20 times or more and 250 times or less to form a stretched product; (3) extracting the plasticizer from the stretched product to form a microporous membrane; (4) a heat treatment step of subjecting the microporous membrane to a heat treatment to stretch and relax it in the width direction to obtain a heat-treated microporous membrane; and (5) a winding step of winding the heat-treated microporous membrane; A manufacturing process for a separator for an electricity storage device, comprising: (6) preparing a positive electrode, a negative electrode, and a non-aqueous electrolyte; (7) disposing the electricity storage device separator between the positive electrode and the negative electrode to produce a laminate; (8) assembling an electricity storage device including the laminate and the nonaqueous electrolyte solution; A method for manufacturing an electricity storage device, comprising:

2. The polypropylene and the polyethylene can be prepared by the following methods (a) to (c): (a) A method in which the polypropylene and the polyethylene are fed into the extruder using separate feeders; (b) A method in which the polypropylene and the polyethylene are dry-blended and then fed into an extruder using one feeder; (c) A method in which a plurality of resin raw materials obtained by dry blending the polypropylene and the polyethylene are fed into an extruder using separate feeders; The method for producing an electricity storage device according to claim 1 , wherein the material is fed into the extruder by any one of the following methods.

3. The method for producing an electricity storage device according to claim 1 or 2, wherein a mass ratio of the polyethylene to the polypropylene is 99 / 1 to 60 / 40.

4. 4. The method for producing an electricity storage device according to claim 3, wherein the polyethylene has a weight average molecular weight (Mw) of 100,000 to 9,700,000 and a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 3 to 12.

5. The polypropylene has a weight average molecular weight (Mw) of 300,000 to 2,000,000 and a ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) of 3 to 12; The method for producing an electricity storage device according to claim 3, wherein the polypropylene has an isotactic pentad fraction (mmmm) of 85.0 mol% to 99.7 mol%.

Citation Information

Patent Citations

  • Method for producing porous film

    JP2002088189A

  • Microporous membrane and lithium battery separator

    JP2002226639A

  • Separator for battery

    JP2005190792A

  • Porous film

    JP2009114434A

  • Separator for lithium secondary battery and lithium secondary battery including the same

    JP2012164655A